2011
DOI: 10.1108/07378831111174431
|View full text |Cite
|
Sign up to set email alerts
|

Use of web technology in providing information services by south Indian technological universities as displayed on library websites

Abstract: Purpose -This paper aims to discuss the present status of using new generation web technology, social media and Web 2.0 features among the technological university library websites in south India. It seeks to assess the library websites as a primary platform and one-stop portal for information services and to examine how much library websites are effective in providing web-based information services. Design/methodology/approach -The library websites of the technological universities in south India were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Studies proposed that information technology has the capacity to bring massive structural changes to a university and in another context, to the healthcare industry, they suggest that the reimbursement rates depend on how it is put to use. In context to Indian universities, it was suggested that deploying web-development technologies and mainstream web-information services on library websites will provide a one-stop portal for information to the students (Balaji & Kumar, 2011;Kohli & Devraj, 2004).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Studies proposed that information technology has the capacity to bring massive structural changes to a university and in another context, to the healthcare industry, they suggest that the reimbursement rates depend on how it is put to use. In context to Indian universities, it was suggested that deploying web-development technologies and mainstream web-information services on library websites will provide a one-stop portal for information to the students (Balaji & Kumar, 2011;Kohli & Devraj, 2004).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…They suggested a few measures for enhancing the quality of library portals. Balaji & Kumar evaluated the library portals of South Indian Technical Universities for knowing the implementation of web 2.0 tools in library websites 11 . This study divides its research scope into four categories and subcategories.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(See Appendix II) developed for this study to evaluate the library websites performance, adapted from these earlier studies (Al-Qallaf and Ridha 2018; Mainka et al, 2013;Balaji and Kumar, 2011). The indicators used for data collection were: 1.…”
Section: Data Collectionmentioning
confidence: 99%